The old German folksongs philological - Grosch, Nils (Muzikološki zbornik, 2013)
The middle age and early modern volkslieder, publishedby Erk and Böhme in "Deutscher Liederhort" etc., mark the process of an invented tradition.Though pretending to be founded on the basis of scholarly and philological accurateness, these editions included manipulations of sources and substantially falsifying and misleading renditions of the original songs.
Keywords: Böhme, Franz Magnus, 1827-1898; Erk, Ludwig, 1807-1883; nemška ljudska pesem (filološki vidik); Stoltzer, Thomas, 1480-1526; tenorska pesem